2016
DOI: 10.1021/acs.jpcc.6b02365
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-Induced in Situ Fabrication of Bi2O4-Decorated BiOBr Nanosheets with Excellent Photocatalytic Performance

Abstract: A simple alkali (NaOH) post-treatment approach assisted with light irradiation to in situ obtain Bi 2 O 4 nanoparticles decorated BiOBr nanosheets, brown colored BiOBr-0.01, is presented for the first time. Bi 2 O 4 nanoparticles are formed due to a combined action of NaOH induced dehalogenation and light triggered photogenerated hole (h + ) oxidation processes on the surface of BiOBr nanosheets. Importantly, by varying the NaOH concertation in the post-treatment, the content of Bi 2 O 4 phase in the hybrid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 110 publications
(36 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…It can be also found that in the final products from Bi 2 O 3 /BiOBr/Zn 2 GeO 4 ‐1 to Bi 2 O 3 /BiOBr/Zn 2 GeO 4 ‐3 with the increase in BiOBr addition, the diffraction intensity of Zn 2 GeO 4 diminished and peak of Bi 2 O 3 also decreased, whereas the peak intensity of (011) plane for BiOBr increased. An obvious intensity reverses of (011) and (110) peaks were observed, which might be caused by the different crystalline orientation of BiOBr, and could relate with the photocatalytic activity of the photocatalysts, as also found in other system …”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…It can be also found that in the final products from Bi 2 O 3 /BiOBr/Zn 2 GeO 4 ‐1 to Bi 2 O 3 /BiOBr/Zn 2 GeO 4 ‐3 with the increase in BiOBr addition, the diffraction intensity of Zn 2 GeO 4 diminished and peak of Bi 2 O 3 also decreased, whereas the peak intensity of (011) plane for BiOBr increased. An obvious intensity reverses of (011) and (110) peaks were observed, which might be caused by the different crystalline orientation of BiOBr, and could relate with the photocatalytic activity of the photocatalysts, as also found in other system …”
Section: Resultsmentioning
confidence: 52%
“…The lattice distance of 0.28 nm can be ascribed to the (110) crystallographic plane of BiOBr . The lattice distance of 0.32 nm corresponds to the (120) crystal plane Bi 2 O 3 QDs, which also support the phase formation of ternary Bi 2 O 3 /BiOBr/Zn 2 GeO 4 heterojunction.…”
Section: Resultsmentioning
confidence: 62%
“…(a) TEM and (b) HRTEM of B001; (c) proposed mechanism of facet‐dependent bacterial inactivation by B001 nanosheets; copyright (2015) Royal Society of Chemistry; (d) proposed formation mechanism of BiOBr‐Br 2 O 4 nanosheets; SEM (e) and TEM (f) images of BiOBr‐Br 2 O 4 composite; copyright (2016) American Chemical Society.…”
Section: D Metal Oxyhalide Photocatalysts For Photocatalytic Disinfementioning
confidence: 99%
“…After that, a series of exogenously doped and self‐doped photocatalysts were fabricated with the BiOBr nanosheets with a high percentage of {001} facets. Boron‐doped BiOBr (B‐BiOBr) was synthesized by adding H 3 BO 3 in the precursors of BiOBr before hydrothermal treatment .…”
Section: D Metal Oxyhalide Photocatalysts For Photocatalytic Disinfementioning
confidence: 99%
See 1 more Smart Citation